2019
DOI: 10.1002/lsm.23050
|View full text |Cite
|
Sign up to set email alerts
|

A miniaturized, tethered, spectrally‐encoded confocal endomicroscopy capsule

Abstract: Background and Objective The tethered spectrally‐encoded confocal endomicroscopy (SECM) capsule is an imaging device that once swallowed by an unsedated patient can visualize cellular morphologic changes associated with gastrointestinal (GI) tract diseases in vivo. Recently, we demonstrated a tethered SECM capsule for counting esophageal eosinophils in patients with eosinophilic esophagitis (EoE) in vivo. Yet, the current tethered SECM capsule is far too long to be widely utilized for imaging pediatric patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…CLE, a new diagnostic modality, can provide real-time, high-magni cation images of the gastric epithelium, and can readily permits inspection of single cells as well as provide better assessment of malignant tissues for guiding biopsies (8,9). Previous study has demonstrated that compared with WLE, CLE diagonsis had a higher accuracy in detecting EGC/HGIN (6).…”
Section: Discussionmentioning
confidence: 99%
“…CLE, a new diagnostic modality, can provide real-time, high-magni cation images of the gastric epithelium, and can readily permits inspection of single cells as well as provide better assessment of malignant tissues for guiding biopsies (8,9). Previous study has demonstrated that compared with WLE, CLE diagonsis had a higher accuracy in detecting EGC/HGIN (6).…”
Section: Discussionmentioning
confidence: 99%
“…Sedation in gastroscopy is widely accepted in highincome countries, which are found to be associated with increased patient comfort and reduced complications related with poor patient cooperation, though it causes additional medical resource consumption [8]. As CLE procedures usually require prolonged endoscopy time and better patient cooperation, sedation is considered even indispensable in these patients [9,10]. However, whether sedation is associated with improved diagnostic quality of CLE is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple light-based approaches are being developed to elucidate cellular, subcellular, and structural changes in EoE ( 5 8 ). However, these are not suitable for unraveling biochemical composition and spatial distribution of biologically active molecules.…”
Section: Introductionmentioning
confidence: 99%